Performance Analysis of a 150 WP Portable Solar Power Plant (PLTS) in the Tarutung District Area - Simanjuntak, Ronaldo Saurdot; Pristisal Wibowo; Anisah, Siti (International Conference Epicentrum of Economic Global Framework, 2026)
This study aims to analyze the performance of a 150-WP portable solar power plant (PLTS) in Tarutung District. The analysis was conducted based on output power parameters, system efficiency, and the influence of solar radiation intensity and environmental conditions. The research method included measuring voltage, current, and power under daily operational conditions. The results showed that the performance of the 150-WP portable PLTS was affected by weather and the position of the solar modules. This study is expected to be a reference for the use of portable PLTS in the area. The research results show that the solar panel voltage (open circuit) is 18.85 V – 19.90 V, peak voltage (19.90 V) at 14:00 the highest light intensity (49,200 Lux at 12:00) there is a correlation between the decrease in light intensity (caused by the weather) and the decrease in panel voltage, when charging the battery (Close Circuit) the battery voltage is lower than the panel voltage, the highest charging current (3.16A), May 23 there was a fluctuation due to cloudy conditions, when testing the load (battery discharge), the total discharge time was 5.6 hours (experiment 1), 4.1 hours (experiment 2, and 3 hours (experiment 3). These results indicate that the Off Grid PLTS in Tarutung District is very feasible to be implemented both technically and environmentally